Recombination-restarted replication makes inverted chromosome fusions at inverted repeats - Mizuno, Ken’Ichi; Miyabe, Izumi; Schalbetter, Stephanie A.; Carr, Antony M.; Murray, Johanne M. (Nature (London), 2013)
A new mechanism of chromosomal rearrangement is identified through the observation that broken or collapsed DNA replication forks restarted by homologous recombination have a high propensity for U-turns at short inverted repeats; the error-prone nature of this mechanism is suggested to contribute to gross chromosomal rearrangements and copy-number variations present in cancer and other genomic disorders. Paused replication forks a source of gene abnormality Stress that causes broken or collapsed DNA replication forks can induce copy-number variations (CNVs) and gross chromosomal rearrangements (GCRs), both of which are commonly found in cancer cells. Antony Carr and colleagues find that a collapsed fork that has been restarted by homologous recombination is more error prone than a fork that initiates at origins of replication. These restarted forks frequently perform U-turns at short inverted repeats, a possible cause of CNVs and GCRs. The authors suggest that the error-prone nature of restarted forks could be a source of cancer-causing gene abnormalities and spontaneous genetic disorders in the absence of a double-strand break. Impediments to DNA replication are known to induce gross chromosomal rearrangements (GCRs) and copy-number variations (CNVs). GCRs and CNVs underlie human genomic disorders 1 and are a feature of cancer 2 . During cancer development, environmental factors and oncogene-driven proliferation promote replication stress. Resulting GCRs and CNVs are proposed to contribute to cancer development and therapy resistance 3 . When stress arrests replication, the replisome remains associated with the fork DNA (stalled fork) and is protected by the inter-S-phase checkpoint. Stalled forks efficiently resume when the stress is relieved. However, if the polymerases dissociate from the fork (fork collapse) or the fork structure breaks (broken fork), replication restart can proceed either by homologous recombination or microhomology-primed re-initiation 4 , 5 . Here we ascertain the consequences of replication with a fork restarted by homologous recombination in fission yeast. We identify a new mechanism of chromosomal rearrangement through the observation that recombination-restarted forks have a considerably high propensity to execute a U-turn at small inverted repeats (up to 1 in 40 replication events). We propose that the error-prone nature of restarted forks contributes to the generation of GCRs and gene amplification in cancer, and to non-recurrent CNVs in genomic disorders.